2005
DOI: 10.1111/j.1365-246x.2005.02395.x
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of graphite formation by tectonic stress - a laboratory experiment

Abstract: S U M M A R YGraphitization of less-ordered hexagonal carbon was studied under in-situ pressure and temperature conditions on anthracite, black shale and a synthetic calcite/anthracite mixture at upper greenschist facies conditions. Anthracite exhibited a continuous loss of volatiles in the temperature range from 100 • C up to 850 • C (9.9 weight per cent at 450 • C) as detected by Differential-Thermal-Analysis (DTA) and Thermo-Gravimetry (TG). Energy dispersive X-ray diffraction (EDX) revealed a broad amorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 39 publications
3
49
0
Order By: Relevance
“…On the basis of these two boreholes, it is evident that the graphite is associated with a number of steeply inclined shear planes (ELEKTB Group 1997;Nover et al 2005;Stoll et al 1995). As indicated in the "Background" section, this graphite forms an interconnected coating along shear planes over a distance of hundreds or thousands of meters, and it is locally concentrated in millimeter-thick layers that constitute good electrical conductors (Emmermann and Lauterjung 1997).…”
Section: Ktb-borehole Anomaly Germanymentioning
confidence: 94%
See 1 more Smart Citation
“…On the basis of these two boreholes, it is evident that the graphite is associated with a number of steeply inclined shear planes (ELEKTB Group 1997;Nover et al 2005;Stoll et al 1995). As indicated in the "Background" section, this graphite forms an interconnected coating along shear planes over a distance of hundreds or thousands of meters, and it is locally concentrated in millimeter-thick layers that constitute good electrical conductors (Emmermann and Lauterjung 1997).…”
Section: Ktb-borehole Anomaly Germanymentioning
confidence: 94%
“…The shearing process is the reason beyond the interconnection of the graphite on the shear planes (ELEKTB Group 1997). Nover et al (2005) carried out a laboratory experiment to understand better the mechanisms that lead to the abundant formation of graphite in overthrust structures. They concluded that graphite is found on shear planes and attributed this graphite to shear movement, shear strain, and strain energy (Bustin et al 1995;Mathez et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, "graphitic particles" may also be produced by increased amounts of shear stress within this horizon (e.g. Nover et al, 2005). Graphite can also be from the reduction of CH 4 and CO 2 released from thermal alteration and cracking of both kerogen and bitumen which (depending on the temperature, pressure, and oxygen fugacity) can be oxidized or reduced to form graphite (Kribek et al, 1994).…”
Section: Vitrinite Reflectance and Organic Petrographymentioning
confidence: 99%
“…Formation of highly conductive graphite films has been found to occur in the presence of CO/CO 2 fluid during fracturing (Roberts et al 1999;Glover & Ádám 2008). Laboratory results by Nover et al (2005) have shown graphite crystals can form at temperatures and pressures simulating continental crustal conditions. During these trials, formations of graphite lead to an increase in conductivity of the host rock of up to three orders on magnitude (Nover et al 2005;Glover & Ádám 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory results by Nover et al (2005) have shown graphite crystals can form at temperatures and pressures simulating continental crustal conditions. During these trials, formations of graphite lead to an increase in conductivity of the host rock of up to three orders on magnitude (Nover et al 2005;Glover & Ádám 2008). These results are consistent with the modelled conductive anomaly under Paralana, suggesting that it is a large graphite-rich body formed during the uplift of the MPD during the formation of the Flinders Ranges.…”
Section: Discussionmentioning
confidence: 99%